Tinjauan Yuridis Perlindungan Hukum terhadap Penumpang Transportasi Udara (Studi Komparasi dengan Negara Uni Eropa) - Suparyana, I Gde Oka; Laksmi Dewi, Cokorde Istri Dian (VYAVAHARA DUTA, 2024)
Airline companies that do not carry out their obligations properly and correctly can be said to have committed a "default". Defaults that are carried out because airlines do not fulfill their obligations to passengers will of course give rise to legal problems, especially those related to issues of responsibility. Default is a condition where the debtor (debtor) does not carry out the performance properly to the creditor in accordance with what has been agreed upon by the airline or carrier for passengers and owners of goods both as parties to the transportation agreement and as consumers, in addition to other problems for consumers is the delay in the implementation of air transportation which sometimes exceeds the tolerance limit. There is a need for legal remedies that can be taken against the above problems. The research method used in this research is a type of normative research using library research and using a comparative study approach.